ORAL CYCLOSPORINE AS AN ALTERNATIVE FOR INITIAL STANDARD PROPHYLAXIS IN ALLOGENEIC STEM CELL TRANSPLANTATION WHEN INTRAVENOUS FORMULATION IS UNAVAILABLE - Leon-rodriguez, Eucario; Rivera-franco, Monica M (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study was to compare the incidence of acute graft versus host disease (aGVHD) between oral and intravenous (IV) initial standard cyclosporine A (CsA) prophylaxis in a tertiary care center in Mexico. Methods: A total of 117 consecutive patients who underwent allogeneic hematopoietic stem cell transplantations (HSCT) were retrospectively analyzed. GVHD prophylaxis consisted of CsA and methotrexate (MTX). CsA was administered IV, until 2005, when it was withdrawn from the market, and CsA was administered orally. Results: Most of the patients were male (55%), with a median age of 33 years (range, 15–63). 92 patients (79%) received CsA orally, and 25 (22%) intravenously. There were no significant differences in CsA concentrations during weeks 1, 2, 3, and 4 between the oral and IV group. From the entire cohort, 1 patient (4%) from the IV group and 16 (17%) from the oral group developed aGVHD, respectively. Sex, gender disparity, and HSCT source were statistically associated with aGVHD in the multivariate analysis. Conclusions: Using oral instead of IV CsA for aGVHD prophylaxis is feasible and could be financially efficient; nonetheless, our results showed a higher incidence of aGVHD in the oral group; however, our study has limitations and further prospective studies including a larger cohort are encouraged.